A mechanism for sharing best practices between university technology transfer offices. Issue 4 (1st November 2017) - De Beer, Christle; Secundo, Giustina; Passiante, Giuseppina; Schutte, Cornelius S. L.
Abstract: Research has shown that university technology transfer offices (TTOs) learn through experimentation and failure, and by sharing these experiences with others. There are many barriers to successfully sharing the best practice between TTOs. The Maturity Model (MM) created by Secundo et al. (Meas Bus Excell, 20:42–54, 2016 ) provides a means by which the performance of a TTO can be better understood to allow for effective sharing of best practices. The aim of this study is to improve and validate the MM to formalize a mechanism through which best practices can be identified and shared between TTOs. This was accomplished by testing the MM in 54 TTOs across Europe and the United Kingdom. Findings regard several improvements of the intangible indicators and the maturity levels of the MM. This research improves the rigor of the MM and formalizes its application as a mechanism for sharing best practices through the Improved MM.